IMPROVING STUDENTS"™ READING COMPREHENSION ON NARRATIVE TEXT THROUGH GUIDED PICTURES - Elsa, Elsa; Yuliana, Yohanes Gatot Sutapa; Riyanti, Dwi (Jurnal Kajian Pembelajaran dan Keilmuan, 2022)
This research aimed to improve students"™ reading comprehension of narrative text through guided pictures. The research method used was classroom action research; it was conducted in two cycles. The subject for this research was year-8 students of SMPN 6 Pontianak class VIII B. In collecting the data, the writer observed the classroom activity during the implementation of this classroom action research by using an observation checklist and a field note to collect all the information.   The problems found in this study were students"™ difficulty in comprehending a long passage of reading narrative and it is hard to understand the question and vocabulary in the text. Therefore, the result showed that the Guided Picture was able to improve students' reading comprehension, which was seen in the improvement of the student's comprehension of narrative text and the improvement of the students' obtained scores. Moreover, the teaching media can be used in improving students"™ reading of the narrative text. The guided picture is recommended to be used as a medium in the teaching and learning process, especially in the context of reading with similar scope of setting and problem